The Development of Team- Based Learning Activities to Enhance English Grammatical Ability for Grade 4 Students - Ruenkrue, Apinya; Thamrongsotthisakul, Wichian (Suan Dusit Graduate School Academic Journal, 2023)
This research aimed to 1) create and identify the efficiency of the development of team- based learning activities to enhance English grammatical ability for grade 4 students based on the criterion 75/75 and 2) test the team- based learning activities to enhance English grammatical ability for grade 4 students by comparing English grammatical ability between before and after using learning activities. The sample group included twenty-three grade 4 students who were studying the second semester, academic year 2021. The sample were chosen by simple random sampling. The research instruments were team- based learning activities to enhance English grammatical ability for grade 4 students and English grammatical ability test. The data were analyzed by using mean, standard deviation, and t-test dependent. The results revealed that 1. the team-based learning activities to enhance English grammatical ability for grade 4 students had the efficiency E1 / E2 at 76.68/75.56 which met the criterion 75/75 2. For the comparison of English grammatical ability between before and after classes, the post-test score was significantly higher than the pre-test score at the statistical significance level of .05.